Olfactory discrimination of female reproductive status by male tilapia (Oreochromis mossambicus) - Miranda, A. (2014)
The current study investigated whether discrimination of sexual status of female tilapia by males is mediated by olfaction. Size-matched groups of female tilapia were assigned as pre- or post-ovulatory according to the time since their last ovulation (15–19·days pre-ovulatory, N=7; 1–3·days post-ovulatory, N=8). Female-conditioned water and body fluids (urine, bile, faeces and plasma) were assessed for olfactory potency in males by recording the electro-olfactogram (EOG). Water extracts, urine and faeces from pre-ovulatory females all evoked significantly larger amplitude EOGs in male fish (N=6), with correspondingly lower thresholds of detection, than those from post-ovulatory females. Plasma and bile evoked very large amplitude EOGs in males but with no differences between the two groups of females. Anosmic males (N=6) did not behave differently towards pre- or post-ovulatory females, while sham-operated males (N=6) showed a marked increase in urination rate towards pre-ovulatory females. We conclude that the ability of male tilapia to discriminate between females of differing reproductive status is mediated by odorants released into the water, probably via the urine and faeces, by pre-ovulatory females.